2015
DOI: 10.1371/journal.pone.0144494
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the Phosphoinositide 3-Kinase Gamma Gene Affects Plasma HDL-Cholesterol without Modification of Metabolic or Inflammatory Markers

Abstract: ObjectivePhosphoinositide 3-kinase γ (PI3Kγ) is a G-protein-coupled receptor-activated lipid kinase mainly expressed in leukocytes and cells of the cardiovascular system. PI3Kγ plays an important signaling role in inflammatory processes. Since subclinical inflammation is a hallmark of atherosclerosis, obesity-related insulin resistance, and pancreatic β-cell failure, we asked whether common genetic variation in the PI3Kγ gene (PIK3CG) contributes to body fat content/distribution, serum adipokine/cytokine conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…A recent study showed association of genetic mutations in PI3Kγ gene affecting plasma cholesterol. However, the single nucleotide polymorphisms (SNPs) reported in this study are present in the intronic region or the SNP leads to synonymous mutations[68] with altering the primary amino-acid sequence. These observations suggest that more studies are needed to assess for SNPs in the genome related to the sequences associated with coding regions of the protein.…”
Section: Pi3kγ As a Scaffold In Other Systemsmentioning
confidence: 99%
“…A recent study showed association of genetic mutations in PI3Kγ gene affecting plasma cholesterol. However, the single nucleotide polymorphisms (SNPs) reported in this study are present in the intronic region or the SNP leads to synonymous mutations[68] with altering the primary amino-acid sequence. These observations suggest that more studies are needed to assess for SNPs in the genome related to the sequences associated with coding regions of the protein.…”
Section: Pi3kγ As a Scaffold In Other Systemsmentioning
confidence: 99%
“…In monogastrics, liver is the primary site for fatty acids oxidation and ketone bodies production[29, 30]. The liver-synthesized cholesterol accounts for more than 80% of the total cholesterol produced by the body, and is the main source of plasma cholesterol [31].…”
Section: Introductionmentioning
confidence: 99%
“…rs17398575, rs17477177, and rs342286 are located near PIK3CG and were associated with cardiovascular diseases risk ( 74 76 ). The PIK3CG SNP rs342286 was associated with epinephrine-induced aggregation ( 77 ) and the SNPs rs4288294 and rs116697954 associate with higher HDL2 cholesterol plasma levels and rs1129293, also evaluated in our study, was associated with lower HDL levels ( 78 ). Genetic association studies have been extensively used to search host factors that predispose to severe outcomes during influenza infection [reviewed in Ref.…”
Section: Discussionmentioning
confidence: 55%